Preservice Teachers’ Reflective Practices, Self- efficacy, and Professional Growth - Nduagbo, Kieran; Casale, Carolyn (Experiential Learning and Teaching in Higher Education, 2023)
This qualitative research study looks at how reflective practices support preservice teachers’ professional growth and development and its impacts on their self-efficacy. This study takes place in a regionally recognized south-western Hispanic Serving Institution that serves a high needs school district. Preservice teachers were asked to reflect on their field experiences to integrate theory and practice. The common themes that emerge contend that preservice teachers with a high sense of self efficacy maintain a better understand of classroom management with its connection to building relationships. Another significant finding indicates that preservice teacher’s reflective practices lead to self-efficacy and professional growth. These finding are significant to improving teacher preparation programs.